Student Engagement Dynamics in Hybrid English Speaking Classes: A Study on Synchronous and Asynchronous Learning in Indonesia - Syauqiyah Awaliyah Alfiani Nur; Nurdin Noni; Chairil Anwar Korompot (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2024)
The study investigates student engagement in hybrid English-speaking classes at an Indonesian university, emphasizing synchronous and asynchronous learning. Hybrid learning combines live (synchronous) and flexible (asynchronous) methods to enhance student engagement in cognitive, behavioral, and emotional dimensions. Conducted as a qualitative study, this research involved 20 second-semester students from the Faculty of Language and Literature at Universitas Negeri Makassar. Data were collected through semi-structured interviews to explore students’ engagement in hybrid English-speaking classes across synchronous and asynchronous learning. The findings reveal that hybrid learning fosters high levels of cognitive engagement by promoting active participation, critical thinking, and access to resources supported by responsive lecturers. Behavioral engagement is similarly enhanced through interactive digital tools and inclusive class discussions, encouraging frequent practice and skill reinforcement. Emotional engagement, however, varies, as some students benefit from the flexibility of online learning, while others face challenges due to reduced face-to-face interaction with lecturers. Key challenges identified include maintaining consistent motivation in virtual environments, managing distractions in home settings, and addressing feelings of being overlooked due to limited real-time lecturer attention. Additionally, technology dependency and variable comfort levels with hybrid learning pose challenges for engagement. The study concludes that effective hybrid learning designs that address cognitive, behavioral, and emotional engagement can significantly enhance student involvement and learning outcomes. These insights contribute to a better understanding of engagement dynamics in hybrid English-speaking courses, offering practical implications for designing more effective learning experiences. However, the study's focus on a specific group of English-speaking students at one institution limits how broadly the findings can be applied. To better understand the strengths and challenges of hybrid learning, future studies should consider a more diverse sample, mix qualitative and quantitative data, and look at how instructor involvement impacts engagement across different learning environments.